Without capacity, there is no development - De Grauwe, Antonde; Unesco. International Institute for Educational Planning (Paris UNESCO, International Institute for Educational Planning, 2009)
"IIEP/UNESCO undertook a wide range of studies to analyze the record of capacity development and to propose innovative and relevant policies and strategies."--www.ieep.unesco.org.
1. Introduction -- 2. Capacity development : what are we talking about? -- 3. Analysing capacity development processes -- 4. Towards successful capacity development : principles and strategies -- Conclusion.
Keywords: Economic assistance -- Developing countries; Technical assistance -- Developing countries